2022
DOI: 10.31219/osf.io/5dft7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Studi Morfometrik Ikan Nila (Oreochromis nilototicus) Hasil Pancingan Masyarakat dan Hasil Budidaya Tambak di Sungai Jeneberang, Kelurahan Pangkabinanga, Kabupaten Gowa

Abstract: Sungai Jeneberang merupakan aspek lingkungan yang penting bagi masyarakat sekitar yang mendiami pemukiman tersebut. Salah satu pemanfaatan sungai oleh masyarakat sekitar adalah dengan melakukan kegiatan memancing. Selain memancing bebas di sungai, masyarakat yang berada disekitaran bantaran sungai juga melakukan kegiatan budidaya yaitu membuat tambak. Salah satu ikan yang sering kali dijumpai pada dua lokasi berbeda yakni saat memancing bebas disungai dan budidaya tambak adalah ikan nila (Oreochromis niloticus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The results obtained indicated that the morphometric characters of the four treatments did not differ from one another. This is consistent with the results obtained on measuring tilapia in controlled cultivation areas with the same water quality where the values obtained do not differ from one another [18].…”
Section: Morphometric Charactersupporting
confidence: 92%
“…The results obtained indicated that the morphometric characters of the four treatments did not differ from one another. This is consistent with the results obtained on measuring tilapia in controlled cultivation areas with the same water quality where the values obtained do not differ from one another [18].…”
Section: Morphometric Charactersupporting
confidence: 92%